1998
DOI: 10.1016/s0014-5793(98)00945-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of caveolin‐induced vesicle formation

Abstract: Caveolae are vesicular organelles with a characteristic uniform diameter in the range of 50^100 nm. Although recombinant expression of caveolin-1 is sufficient to drive caveolae formation, it remains unknown what controls the uniform diameter of these organelles. One hypothesis is that specific caveolin-caveolin interactions regulate the size of caveolae, as caveolin-1 undergoes two stages of self-oligomerization. To test this hypothesis directly, we have created two caveolin-1 deletion mutants that lack regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 53 publications
(140 reference statements)
8
48
0
Order By: Relevance
“…3). This is consistent with previous observations demonstrating that recombinant expression of caveolin-3 in cultured cells is sufficient to drive caveolae formation (41).…”
Section: Resultssupporting
confidence: 93%
“…3). This is consistent with previous observations demonstrating that recombinant expression of caveolin-3 in cultured cells is sufficient to drive caveolae formation (41).…”
Section: Resultssupporting
confidence: 93%
“…In contrast to caveolin-2, caveolin-1 had a predominant plasma membrane localization in both polarized FRT and MDCK cells. Importantly, a substantial fraction of caveolin-2 changed its distribution from the Golgi complex to the plasma membrane in the presence of caveolin-1, in agreement with previous data that demonstrate an interaction of the two caveolins (8,10,29). This differential localization of caveolins -1 and -2 was striking because it was recently shown that in a nonpolarized fibroblastic cell line (3T3-L1 cells), epitope-tagged caveolin-2 and endogenous caveolin-2 are strictly co-localized with endogenous caveolin-1, both intracellularly and at the level of the plasma membrane (9,10).…”
Section: Fig 10supporting
confidence: 92%
“…Recombinant expression of caveolin-3 in cultured cells is sufficient to drive caveolae formation (39). As caveolin-3 is the only member of the caveolin gene family expressed in striated muscle cells, caveolin-3 is thought to be responsible for caveolae formation in skeletal muscle cells in vivo.…”
Section: Caveolin-3 Null Mice and Lgmd-1cmentioning
confidence: 99%
“…Next, we evaluated if dystrophin and dystrophin-associated glycoproteins were enriched in cholesterol-sphingolipid-rich raft domains in WT and caveolin-3 null mice. When caveolin-3 is expressed, it is targeted to these lipid rafts and induces the formation of morphological caveolae (39), as caveolins are cholesterol-binding proteins (5,42). However, cholesterol-sphingolipid rafts exist in the absence of caveolin protein expression (30,33,43).…”
Section: The Dystrophin-glycoprotein Complex Is Excluded From Detergementioning
confidence: 99%